The interactive effect of environmental management team with board attributes on sustainability pillars: Evidence from Gulf Cooperation Council (GCC) - Abusharbeh, Mohammed; Hanaysha, Jalal Rajeh; Samara, Husni (Elsevier I, 2025)
This study elucidates the moderating effect of environmental team on the nexus between board effectiveness and ESG performance, utilizing panel data from 89 non-financial listed firms in Gulf Cooperation Council (GCC) from 2018 to 2022. Thus, fixed effects model and Two Stages Least Square (2SLS) were used to address robustness findings and to detect endogeneity bias in our estimated models. The results reveal that board background skills and female directors are more likely to support board oversight toward sustainability pillars. We ascertain that the existence of environmental team positively strengthens the impact of gender diversity and board skills on ESG pillars. However, our findings affirm that board environmental team negatively moderates the relationship between CEO duality and ESG performance. Additionally, large-sized board and sustainability are adversely moderated by the board environmental committee. Overall, our research offers robust guidelines for regulatory bodies in GCC towards develop ESG regulations and to encourage firms to build a specialized team for promoting sustainability pillars.